Higher education as a space for promoting the psychosocial well-being of refugee students. (February 2019) - Jack, Odette; Chase, Elaine; Warwick, Ian
Objective: This study aimed to investigate how well a single higher education institution (HEI) was perceived to be meeting the psychosocial support needs of refugee students and to identify possible ways in which the HEI might better promote refugee students' psychosocial well-being. Design: Adopting an exploratory, focused case study design, the research employed a qualitative interpretive approach utilising three data collection methods: narrative inquiry, Photovoice and key informant interviews. The social ecological model and the health-promoting university approach guided the enquiry and analysis. Setting: A single HEI in London, UK. Results: Refugee student-participants reported stressful and traumatic experiences at different points in their migratory experience. Participants were motivated by being involved in education but identified barriers to seeking institutional support to improve their health and well-being. Student-participants and staff identified ways in which support for refugee student well-being could be improved. Conclusion: Refugee students were found to have specific health and well-being support needs which were not met due to a range of organisational constraints. The social ecological model and the health-promoting university offer frameworks for HEIs to respond better to the diverse health and well-being needs of students.